“How do I say it in Portuguese?”: A Study on Interactional Practices and Actions in Search of Intersubjectivity Between Koreans and Brazilians (Revista de Estudos da Linguagem, 2024)
This research aims to interactively analyze excerpts of a video published on YouTube entitled “24 HOURS SPEAKING PORTUGUESE IN BRAZIL!!!”. In this video, three Korean friends visit different commercial establishments in São Paulo to interact with Brazilian Portuguese speakers. From the interactions, it is possible to identify several actions performed to make themselves understood while speaking this language. The in-depth analysis of these strategies constitutes our research theme. Through the interactions available in the video, we seek to identify which interactional actions and practices were used to achieve intersubjectivity when speaking Portuguese as an additional language with Brazilians. As secondary objectives, the research aims to describe these practices and actions in order to verify which ones are successful in achieving the interactional purposes and also to observe the practices put in place by Portuguese speakers to facilitate the understanding of Rico, organizer of the analyzed video, and his friends in and through speech-in-interaction. In addition, it aims to show whether these practices could be taken to the Portuguese as an Additional Language (PAL) classroom. To achieve the proposed objectives, this research is anchored in the methodological perspective of Conversation Analysis (Sacks; Schegloff; Jefferson, 1974), whose main objective is to describe actions used by common speakers when participating in intelligible and socially organized interactions. For this analysis, the data were transcribed using the conventions of Jefferson (1984) and Mondada (2022). From the transcription and scrutiny of the available data, it was possible to identify several practices and actions relevant to the interactions that occurred in the video, such as mimes, gestures and repetitions. These actions were described in order to highlight the joint construction of understanding in this context.